Differences in clinical importance of Bcl-2 in breast cancer according to hormone receptors status or adjuvant endocrine therapy. Issue 1 (December 2015) - Honma, Naoko; Horii, Rie; Ito, Yoshinori; Saji, Shigehira; Younes, Mamoun; Iwase, Takuji; Akiyama, Futoshi
Abstract Background Bcl-2 plays an anti-apoptotic role, resulting in poor clinical outcome or resistance to therapy in most tumor types expressing Bcl-2. In breast cancer, however, Bcl-2 expression has been reported to be a favorable prognostic factor. The positive correlation of Bcl-2 with estrogen receptor (ER)/progesterone receptor (PR) status, and endocrine therapy frequently given for hormone receptor-positive tumors, may obscure the independent pathobiological role of Bcl-2. We constructed a large systematic study to determine whether Bcl-2 has an independent role in breast cancer. Methods Bcl-2 expression was immunohistochemically evaluated and compared with other clinicopathological factors, including clinical outcome, in 1081 breast cancer cases with long follow-up, separately analyzing 634 cases without any adjuvant therapy and 447 cases with tamoxifen monotherapy. Theχ 2 -test for independence using a contingency table, the Kaplan-Meier method with the log-rank test, and a Cox proportional hazards model were used for the comparison of clinicopathological factors, assessment of clinical outcome, and multivariate analyses, respectively. Results In both patient groups, Bcl-2 expression strongly correlated with positive ER/PR status, low grade, negative human epidermal growth factor receptor 2 (HER2) status, and small tumor size, as previously reported. Bcl-2 expression did not independently predict clinical outcome in patients with ER-positive and/or PR-positive tumors or in those who received tamoxifen treatment; however, it was an independent unfavorable prognostic factor in patients with ER-negative/PR-negative or triple-negative (ER-negative/PR-negative/HER2-negative) tumors who received no adjuvant therapy. The latter was even more evident in postmenopausal women: those with hormone receptor-negative or triple-negative tumors lacking Bcl-2 expression showed a favorable outcome. Conclusion Bcl-2 expression is an independent poor prognostic factor in patients with hormone receptor-negative or triple-negative breast cancers, especially in the absence of adjuvant therapy, suggesting that the anti-apoptotic effect of Bcl-2 is clearly exhibited under such conditions. The prognostic value of Bcl-2 was more evident in postmenopausal women. The present findings also highlight Bcl-2 as a potential therapeutic target in breast cancers lacking conventional therapeutic targets such as triple-negative tumors. The favorable prognosis previously associated with Bcl-2-positive breast cancer probably reflects the indirect effect of frequently coexpressed hormone receptors and adjuvant endocrine therapy.